Ionic conductivity studies of poly(vinyl alcohol) alkaline solid polymer electrolyte and its use in nickel–zinc cells - Mohamad , A. A.; Mohamed, N. S.; Yahya, M. Z. A.; Othman, Raihan; Ramesh, S.; Alias, Y.; Arof, A. K. (ELSEVIER Science B.V., 2003)
X-ray diffraction (XRD) pattern reveals that potassium hydroxide (KOH) disrupts the crystalline nature of poly(vinyl alcohol) (PVA)-based polymer electrolytes and converts them into an amorphous phase. The PVA–KOH alkaline solid polymer electrolyte (ASPE) system with PVA/KOH wt.% ratio of 60:40 exhibits the highest room temperature ionic conductivity of 8.510 exp(-4) S/cm. This electrolyte was used in the fabrication of a nickel–zinc (Ni–Zn) cell. The cell was charged at a constant current of 10 mA for 1 h providing it with 1.6 V. The cell was cycled 100 times. At the end of the last cycle, the cell still contained a capacity of 5.5 mA h.